A crosstalk-immune sub-THz All-surface-wave I/O transceiver in 65-nm CMOS - Liang, Yuan (2020)
A surface-wave I/O transceiver is proposed and validated at 140 GHz in 65 nm CMOS. By generating, modulating and propagating surface plasmonic signal, the all-surface-wave I/O is prototyped with crosstalk-immune owning to the sub-wavelength localization of electromagnetic wave at the metal/dielectric interface. A four-way surface-wave signal source is power-combined via coupled oscillator network. A surface-wave modulator is realized by stacking two split-ring-resonator (SRR) unit-cells with opposite placement. It is further integrated into the all-surface-wave I/O with a surface-wave transmission line and matching converter. Measured results show that the proposed dual-channel I/O delivers a localized 140 GHz surface-wave signal, demonstrating crosstalk-immune on-chip transmission by supporting 13.5 Gb/s data-rate communication with 2.6 PJ/bit Power efficiency and a bit-error rate less than 10^(-12).